2020
DOI: 10.1002/adem.202000220
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Thermoresistivity of Freestanding and Polymer Embedded Carbon Nanotube Yarns

Abstract: Carbon nanotube yarns (CNTYs) are hierarchical fibers with outstanding electrical properties, and understating the temperature‐dependence of their electrical resistance (thermoresistivity) is essential for sensing applications and development of self‐sensing polymer composites. The cyclic thermoresistive response of individual CNTYs and the effect of embedding the yarn into a polymer are experimentally investigated herein. The effect of confining the CNTY by a thermosetting polymer is addressed by studying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 52 publications
6
17
0
Order By: Relevance
“…Therefore, the thermoresistivity of the CNTY itself is expected to be a negligible contributor to Δ R/R 0 . From a previous study, the normalized change in electrical resistance (Δ R/R 0 ) of a CNTY, embedded into a vinyl ester polymer was determined to be linearly proportional to the change in temperature (Δ T ) within a 25 to 100 °C temperature range [ 8 ]. The thermal coefficient of resistance ( β = (Δ R/R 0 )/Δ T ) of this embedded CNTY (the same kind as the one used herein) was also calculated in such a work as 6.53 × 10 −4 K −1 [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the thermoresistivity of the CNTY itself is expected to be a negligible contributor to Δ R/R 0 . From a previous study, the normalized change in electrical resistance (Δ R/R 0 ) of a CNTY, embedded into a vinyl ester polymer was determined to be linearly proportional to the change in temperature (Δ T ) within a 25 to 100 °C temperature range [ 8 ]. The thermal coefficient of resistance ( β = (Δ R/R 0 )/Δ T ) of this embedded CNTY (the same kind as the one used herein) was also calculated in such a work as 6.53 × 10 −4 K −1 [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…From a previous study, the normalized change in electrical resistance (Δ R/R 0 ) of a CNTY, embedded into a vinyl ester polymer was determined to be linearly proportional to the change in temperature (Δ T ) within a 25 to 100 °C temperature range [ 8 ]. The thermal coefficient of resistance ( β = (Δ R/R 0 )/Δ T ) of this embedded CNTY (the same kind as the one used herein) was also calculated in such a work as 6.53 × 10 −4 K −1 [ 8 ]. Using this temperature coefficient of resistance and a maximum change in temperature of 2.7 °C (~275 K), the decrease in Δ R/R 0 is estimated as ~−0.18%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the high porosity of the CNTYs may promote infiltration of liquids between the CNT bundles affecting the stiffness, toughness, and electrical conductivity of the yarn by separating the adjacent CNT bundles and increasing the contact electrical resistance [3,[7][8][9]. It was observed that C 2021, 7, 60 2 of 14 the thermoresistive properties of the embedded CNTY strongly depend on the chemical structure of the polymeric matrix, temperature range, porosity, and capillary diffusion of polar liquids [3,8,[10][11][12][13][14][15]. Rodríguez-Uicab et al [10] investigated the effect of the curing kinetics of epoxy resins with different viscosities on the thermoresistive response of the CNTY monofilament composites at different curing temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…The thermoresistive response of CNTYs embedded in thermosetting resins was also studied by a few authors. Balam et al [14] investigated the thermoresistive response of CNTY/vinyl ester composites and isolated CNTYs above RT. The electrical resistance per unit length of the isolated CNTY was~20 Ω mm −1 , and it increased by 37% during the curing process of the resin.…”
Section: Introductionmentioning
confidence: 99%